2012
DOI: 10.1007/s00508-012-0156-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology ofPseudomonas aeruginosa in cystic fibrosis patients from Southeast Austria

Abstract: Pseudomonas aeruginosa is the major pathogen in the cystic fibrosis (CF) lung, the predominant source of its acquisition, however, is under discussion. In order to study the molecular epidemiology, we evaluated 86 P. aeruginosa isolates from 43 CF patients from southeast Austria. The DiversiLab system was used to identify genetic relationships among the isolates. Antibiotic susceptibilities were tested with a broth microdilution method (Micronaut Merlin). A total of 39 unrelated P. aeruginosa genotypes were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
3
3
0
Order By: Relevance
“…Our findings are in concordance with a similar study published recently [ 10 ]. Masoud-Landgraf et al typed 86 P. aeruginosa isolates from 43 CF patients under care in the CF centre of the Medical University of Graz, Austria, and found that the majority of CF patients under their investigation harboured unique P. aeruginosa genotypes.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our findings are in concordance with a similar study published recently [ 10 ]. Masoud-Landgraf et al typed 86 P. aeruginosa isolates from 43 CF patients under care in the CF centre of the Medical University of Graz, Austria, and found that the majority of CF patients under their investigation harboured unique P. aeruginosa genotypes.…”
Section: Discussionsupporting
confidence: 94%
“…Masoud-Landgraf et al typed 86 P. aeruginosa isolates from 43 CF patients under care in the CF centre of the Medical University of Graz, Austria, and found that the majority of CF patients under their investigation harboured unique P. aeruginosa genotypes. Putting our data together with results published by Masoud-Landgraf et al and [ 10 ], it may be argued, that for the majority of CF patients in Austria nosocomial acquisition of P. aeruginosa does not constitute a relevant source of infection.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The first approach comprised typing P. aeruginosa CF isolates, which is based on the amplification of repetitive elements in the genome via the DiversiLab method, which has been used extensively to rapidly detect hospital outbreaks of P. aeruginosa (Doleans-Jordheim et al, 2009;Fluit et al, 2010;Ratkai et al, 2010;Deplano et al, 2011;Masoud-Landgraf et al, 2012). The first approach comprised typing P. aeruginosa CF isolates, which is based on the amplification of repetitive elements in the genome via the DiversiLab method, which has been used extensively to rapidly detect hospital outbreaks of P. aeruginosa (Doleans-Jordheim et al, 2009;Fluit et al, 2010;Ratkai et al, 2010;Deplano et al, 2011;Masoud-Landgraf et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…To gain an insight into the P. aeruginosa population that is present among patients with CF attending the CF reference center at UZ Brussel, a combination of two previously described typing methods was used. The first approach comprised typing P. aeruginosa CF isolates, which is based on the amplification of repetitive elements in the genome via the DiversiLab method, which has been used extensively to rapidly detect hospital outbreaks of P. aeruginosa (Doleans-Jordheim et al, 2009;Fluit et al, 2010;Ratkai et al, 2010;Deplano et al, 2011;Masoud-Landgraf et al, 2012). However, a number of studies have shown that typing solely based on DiversiLab can lead to an underestimation of the 1 Core *A deletion event was considered independent if the deleted region was identified in the genome of a distinct P. aeruginosa isolate at a distinct time point in a distinct patient with CF.…”
Section: Discussionmentioning
confidence: 99%